Interplay of Subduction Tectonics, Sedimentation, and Carbon Cycling. (10th November 2019) - Riedinger, N.; Torres, M.E.; Screaton, E.; Solomon, E.A.; Kutterolf, S.; Schindlbeck‐Belo, J.; Formolo, M.J.; Lyons, T.W.; Vannucchi, P.
Abstract: Distinct differences were observed in geochemical signatures in sediments from two sites drilled in the upper plate of the Costa Rica margin during Integrated Ocean Drilling Program (IODP) Expedition 334. The upper 80 m at Site U1379, located on the outer shelf, shows pore water non‐steady state conditions characteristic of a declining methane flux. These contrast with analyses of the upper sediment layers at the middle slope site (U1378) that reflect steady state conditions. Distinct carbonate‐rich horizons up to 11 meters thick were recovered between 63 and 310 meters below seafloor at Site U1379 but were not found at Site U1378. The carbonates and dissolved inorganic carbon from Site U1379 have a depleted carbon stable isotope signal (up to −25‰) that indicates anaerobic methane oxidation. This inference is further supported by distinct δ 34 S‐pyrite and magnetic susceptibility records that reveal fluctuations of the sulfate‐methane transition in response to methane flux variations. Tectonic reconstructions of this margin document a marked subsidence event after arrival of the Cocos Ridge, 2.2 ± 0.2 million years ago (Ma), followed by increased sedimentation rates and uplift. As the seafloor at Site U1379 rose from ~2, 000 m to the present water depth of ~126 m, the site moved out of the gas hydrate stability zone at ~1.1 Ma, triggering upward methane advection, methane oxidation, and the onset of massive carbonate formation. Younger carbonate occurrences and the non‐steady state pore water profiles at Site U1379 reflect continued episodic venting likely modulated by changes in the underlying methane reservoir. Plain Language Summary: Several carbonate‐rich layers, up to 11 m in thickness, were recovered in sediments collected at Site U1379 in the outer shelf of the Costa Rica margin, offshore the Osa Peninsula. These layers coincide with minima in the magnetic mineral assemblages. To investigate the processes and mechanisms that led to the formation of these carbonates, we used geochemical and sedimentological analyses of pore water and solid phase samples collected at two sites (U1378 and U1379) during the Integrated Ocean Drilling Program (IODP) Expedition 334. Our results, in the context of available dating and tectonic reconstructions, indicate that the discrete carbonate layers formed near the seafloor driven by anaerobic oxidation of methane, which was released from deeper sediments. The methane discharge events can be related to the subsidence and uplift history of the margin following the subduction of the Cocos Ridge beneath the Caribbean plate. Methane discharge at Site U1379 began ~1.1 Ma, when the ongoing margin uplift brought this site to a depth shallower than that where gas hydrates are stable, breaking a permeability barrier that had kept methane trapped within the sediment. Since then, methane continued to be released in discrete events modulated by characteristics of the gas reservoir. Key Points: Authigenic carbonate formation documents episodic methane venting Fluid release events respond to uplift and subsidence off Costa Rica Diagenetic changes impact sedimentary magnetic signal in non‐steady state system